2021
DOI: 10.21203/rs.3.rs-143811/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatty Acid Composition and Eco-Agronomical Traits of Lallemantia Species Modulated Upon Exposed To Arbuscular Mycorrhizal Fungi and Nano Iron Chelate Fertilizers Under Water Deficit Conditions

Abstract: Background: Application nano iron chelate and AMF fertilizer can increase plants' tolerance against water deficit stress. The main objectives of the current study were to investigate the effect of arbuscular mycorrhizal fungi (AMF) and nano iron chelate fertilizer under drought stress on grain yield, leaf chlorophyll contents, root colonization, oil percentage, and fatty acids profile of Lallemantia species. The experiment was carried out as a factorial based on a complete randomized block design consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Some strains can maintain the non-producing strains against drought stress by producing secondary metabolites, such as exopolysaccharides [ 81 ]. A study showed that microorganisms belonging to the roots of grapevine and olive plants can improve the growth of Orize sative L. This enhancement may be due to the extensive roots system and increased water uptake ability [ 82 , 83 ]. In addition, it has been found that using humic acid and PGPR ( B.megaterium and B. subtilis ) enhanced the plant height and yield compared with untreated control.…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…Some strains can maintain the non-producing strains against drought stress by producing secondary metabolites, such as exopolysaccharides [ 81 ]. A study showed that microorganisms belonging to the roots of grapevine and olive plants can improve the growth of Orize sative L. This enhancement may be due to the extensive roots system and increased water uptake ability [ 82 , 83 ]. In addition, it has been found that using humic acid and PGPR ( B.megaterium and B. subtilis ) enhanced the plant height and yield compared with untreated control.…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%